Augmented reality integrated education game using problem-based learning model to improve critical thinking skills - Peni Suharti; A. Asyari; Wiwi Wikanta (Research and Development in Education (RaDEn), 2024)
Limited students' critical thinking skills in learning can be strengthened by using augmented reality technology applications. The main objective of this research is to analyze the problem-based learning model with integrated augmented reality educational games in improving students' critical thinking abilities. This quasi-experimental research used a nonequivalent control group design. The research sample consisted of 60 students from SD Muhammadiyah 09 Surabaya who were selected using purposive sampling. Data was collected by observing the implementation of learning and testing students' critical thinking levels. The data obtained in the research was processed statistically based on research obtained with a significant value of 0.000 < 0.05, confirming that Ho was rejected and H1 was accepted. Thus, the probability value is 0.000 < 0.05, so all coefficients have meaning. Applying the PBL model with integrated augmented reality educational games on critical thinking skills has a significant effect. From the ANOVA test or F-test, Fcount was 45,348 with a significance level of 0.000. This probability is smaller than 0.05, so the learning model to predict the level of participation in learning with a problem-based learning model through educational games integrated with augmented reality influences students' critical thinking skills.